2010
DOI: 10.4240/wjgs.v2.i10.359
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of invasive intraductal papillary mucinous neoplasms of the pancreas

Abstract: Intraductal papillary mucinous neoplasms (IPMN) are mucin producing cystic neoplasms of the pancreas histologically classified as having non-invasive and invasive components. The five-year survival rates for non-invasive and associated invasive carcinoma are 90% and 40%, respectively in resected IPMN lesions. Invasive carcinoma within IPMN lesions can be further classified by histological subtype into colloid carcinoma and tubular carcinoma. Estimated five-year survival rates following resection of colloid car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 25 publications
1
15
0
1
Order By: Relevance
“…51, 62, 64, 65, 98100 About half of the invasive carcinomas that arise in association with an IPMN are ordinary tubular (ductal) adenocarcinoma (Fig. 3A), characterized by infiltrating small to medium tubular units separated by abundant stroma.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…51, 62, 64, 65, 98100 About half of the invasive carcinomas that arise in association with an IPMN are ordinary tubular (ductal) adenocarcinoma (Fig. 3A), characterized by infiltrating small to medium tubular units separated by abundant stroma.…”
Section: Resultsmentioning
confidence: 99%
“…65, 101, 102 Patients with colloid carcinomas have a significantly better prognosis than do patients with tubular invasive carcinomas. 51, 62, 63, 65, 98, 100 Further, both colloid carcinoma and its common precursor, intestinal type IPMN, are characterized by intestinal type differentiation markers - diffuse and strong expression of the intestinal epithelial marker, MUC2, and, the intestinal differentiation marker, CDX2, - neither of which are expressed substantially in any other tumor type in the pancreas. 5052, 103105 These render colloid carcinomas a potential candidate for a different management approach, and thus accentuate the importance of its recognition and proper documentation in the pathology reports.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have suggested that patients with colloid carcinomas have a better prognosis than do patients with tubular adenocarcinoma [128][129][130]. Some of this, however, is lost when stage is controlled for.…”
Section: Prognosismentioning
confidence: 99%
“…umliegender Strukturen. Bei PatiInvasiv wachsende karzinomatöse Tumoranteile finden sich in 24-60% der resezierten Fälle [6], mit 5-Jahres-Überlebens-raten bis 50% und Rezidiven in ca. 60%.…”
Section: Muzinös-zystische Neoplasienunclassified